2023
DOI: 10.1021/acs.macromol.3c00647
|View full text |Cite
|
Sign up to set email alerts
|

3-Alkoxyphthalides as Nonhomopolymerizable, Highly Reactive Comonomers for ABC Pseudo-Periodic Terpolymers and Degradable Polymers via Cationic Co- and Terpolymerizations with Oxiranes and/or Vinyl Ethers

Abstract: 3-Alkoxyphthalides (ROPTs) are promising candidate monomers that react with a cationic species at the carbonyl group and subsequently undergo ring-opening to generate a carbocation adjacent to both aryl and alkoxy groups (oxocarbenium ion). In this study, cationic polymerizations of ROPTs bearing methoxy, isopropoxy, tertbutoxy, or phenoxy groups were investigated with a particular focus on the copolymerizations with oxiranes. Cationic homopolymerization of ROPTs did not occur under any of the examined conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The aryl substituents and/or fused ring structures of X-4 units in copolymer chains are likely responsible for the higher T g s of the CEVE–X-4 copolymers than those of the CEVE–E-1 copolymers and CEVE homopolymer. The VCHO–G-1 copolymer exhibited a lower T g (2 °C; entry 6) than that of a VCHO homopolymer (50 °C; entry 7). In TGA analysis, the copolymers began to degrade at around 200 °C (Figure S27).…”
Section: Resultsmentioning
confidence: 99%
“…The aryl substituents and/or fused ring structures of X-4 units in copolymer chains are likely responsible for the higher T g s of the CEVE–X-4 copolymers than those of the CEVE–E-1 copolymers and CEVE homopolymer. The VCHO–G-1 copolymer exhibited a lower T g (2 °C; entry 6) than that of a VCHO homopolymer (50 °C; entry 7). In TGA analysis, the copolymers began to degrade at around 200 °C (Figure S27).…”
Section: Resultsmentioning
confidence: 99%
“…162 In 2023, the same group produced ABC pseudo-periodic terpolymers using 3-alkoxyphthalides as nonhomopolymerizable and highly reactive comonomers. 163 In this terpolymerization process, 3-alkoxyphthalides reacted with a cationic species at the carbonyl group and then underwent a ring-opening process to deliver a carbocation adjacent to both aryl and alkoxy groups. The introduction of the acetal moieties conferred degradability to the polymers under acidic conditions.…”
Section: Organoboron-mediated Cationic Polymerizationmentioning
confidence: 99%
“…ROPTs have a cyclic hemiacetal ester structure and do not exhibit homopolymerizability, which is similar to DOLOs. In our previous study, oxiranes were demonstrated to undergo cationic copolymerizations with ROPTs . In particular, ROPTs exhibited superior copolymerizability to that of DOLOs in terms of polymer MWs and the frequency of crossover reactions.…”
mentioning
confidence: 99%
“…In addition, both VAc and IPOPT did not undergo cationic homopolymerization under the conditions suitable for the copolymerization (Table S1). , …”
mentioning
confidence: 99%
See 1 more Smart Citation